ANALYSIS OF THE CONDITIONS FOR SYNTHESIS OF EFFICIENT SIDE-LOBES SUPPRESSION FILTERS FOR PHASE MANIPULATED SIGNALS: ANALYSIS OF THE CONDITIONS FOR SYNTHESIS OF EFFICIENT SIDE-LOBES SUPPRESSION FILTERS FOR PHASE MANIPULATED SIGNALS - Bedzhev, Borislav; Velikova, Denitsa; Zhikov, Zhivko (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The radio signals, possessing the so-named ideal auto – correlation function, resembling the Dirac delta – function, have a critical role for the wireless communication systems, especially for radars, radio-navigation systems, radio – synchronization and so on. Despite of this at the moment only few classes of such signals are invented. With regard in the paper we analyze in more detail the method for synthesis of pairs of phase manipulated signals and mismatched side-lobe suppression filters (SLSFs), which modify the real periodic auto – correlation function of the signals in the so-named ideal form, resembling the Dirac delta-function. As a result a new necessary condition for synthesis of efficient SLSFs is proven.